Patient Satisfaction and Visual Function Following Implantation of Trifocal or Extended Range of Vision Intraocular Lenses - Britton, Julia JL; El-Defrawy, Sherif; Wong, Bryan M; Chandrakumar, Manokaraananthan; Omali, Negar B; Pham, Song; Hatch, Wendy (Clinical ophthalmology (Auckland, N.Z.), 2022)
To compare the trifocal TFNT00 and extended depth-of-focus (EDF) ZXR00 intraocular lenses (IOLs) with respect to overall satisfaction with near and distance vision, visual acuity, dysphotopsia symptoms, spectacle dependence, and mesopic best corrected contrast sensitivity (MBCCS). This non-randomized, retrospective, single-centre, comparative study took place at the Kensington Eye Institute in Toronto, Canada. Subjects implanted with either the TFNT00 IOL (n = 11) or ZXR00 IOL (n = 13) were assessed up to 4 years post operatively. Overall satisfaction with distance and near vision, corrected distance visual acuity, uncorrected visual acuity at distance, intermediate (60 cm) and near (40 cm) (UNVA), dysphotopsia symptoms, spectacle dependence and monocular MBCCS were evaluated. Forty-eight eyes of 24 subjects (mean age 68 years, 54% female) were assessed. There was no difference in overall satisfaction; both groups had a median score of 10/10 for overall distance vision, and 7/10 and 8/10 for near vision for EDF and trifocal, respectively. MBCCS at the higher spatial frequencies was significantly better with the ZXR00 IOL. Potentially clinically relevant but not statistically significant differences were found; the trifocal group (vs the EDF group) had better binocular UNVA (20/24 vs 20/32) and less spectacle dependence at least some of the time (54% vs 85%). The ZXR00 may be preferred for those who want optimal contrast sensitivity in dim lighting. Consistent with previous studies, the TFNT00 trifocal IOL may be a better choice for those who want to optimize UNVA. More studies in North America are required to further investigate spectacle dependence.